Improving Students' Understanding of Hijaiyah Letters through the Problem Based Learning Model at SD Negeri Perapat Batu Nunggul - Sekarinah (Jurnal Profesi Guru Indonesia, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning by using problem-based learning. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research are elementary school students. The data in this study were obtained using test and observation techniques. Tests were used to measure learning outcomes and observations were used to analyze the learning activities of teachers and students. The data analysis technique used in this research was descriptive statistics by comparing the results with research success indicators. The results of the research showed that problem-based learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with the pre-cycle details of 44.71%, the first cycle 79.39% and in the second cycle increased to 89.96%. Thus, the use of problem-based learning can be used as one alternative to improve student learning outcomes in Islamic religious education learning.